2016
DOI: 10.1074/jbc.m115.705970
|View full text |Cite
|
Sign up to set email alerts
|

Fast or Slow, Either Head Can Start the Processive Run of Kinesin-2 KIF3AC

Abstract: Mammalian KIF3AC contains two distinct motor polypeptides and is best known for its role in organelle transport in neurons. Our recent studies showed that KIF3AC is as processive as conventional kinesin-1, suggesting that their ATPase mechanochemistry may be similar. However, the presence of two different motor polypeptides in KIF3AC implies that there must be a cellular advantage for the KIF3AC heterodimer. The hypothesis tested was whether there is an intrinsic bias within KIF3AC such that either KIF3A or KI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 38 publications
4
29
0
Order By: Relevance
“…In contrast, the velocity of KIF3CC was exceedingly slow at 7.5 nm/s with KIF3AC at 186 nm/s, whose faster rate was thought to be due to the properties of KIF3A (35) , both of which are extremely slow (50). Additional evidence that heterodimerization may alter the intrinsic catalytic properties of each motor domain as defined by the engineered homodimers KIF3AA, KIF3BB, and KIF3CC was supported by experimental results that showed that no mixtures of KIF3AA plus KIF3CC or KIF3AA plus KIF3BB could recapitulate the microtubule association and ADP release kinetics of KIF3AC or KIF3AB (49, 50).The general hypothesis has been that heterodimerization provides diversity for adaptor and cargo binding, yet the results to date for KIF3AC and KIF3AB clearly show that in spite of high sequence similarity in their motor domains, KIF3A and KIF3B are both catalytically fast, yet KIF3C is extremely slow (35,(49)(50)(51) To address these questions and gain insight into the motility capability of KIF3AC as a cargo transporter, we repeated the presteady-state kinetics experiments for microtubule association, ADP release, and ATP binding and pursued computational modeling coupled with parameter estimation. The results reveal that the catalytic properties of KIF3A and KIF3C were altered upon microtubule association to be catalytically similar, yet once in the processive run KIF3A remained fast with KIF3C continuing to be slow.…”
mentioning
confidence: 47%
See 4 more Smart Citations
“…In contrast, the velocity of KIF3CC was exceedingly slow at 7.5 nm/s with KIF3AC at 186 nm/s, whose faster rate was thought to be due to the properties of KIF3A (35) , both of which are extremely slow (50). Additional evidence that heterodimerization may alter the intrinsic catalytic properties of each motor domain as defined by the engineered homodimers KIF3AA, KIF3BB, and KIF3CC was supported by experimental results that showed that no mixtures of KIF3AA plus KIF3CC or KIF3AA plus KIF3BB could recapitulate the microtubule association and ADP release kinetics of KIF3AC or KIF3AB (49, 50).The general hypothesis has been that heterodimerization provides diversity for adaptor and cargo binding, yet the results to date for KIF3AC and KIF3AB clearly show that in spite of high sequence similarity in their motor domains, KIF3A and KIF3B are both catalytically fast, yet KIF3C is extremely slow (35,(49)(50)(51) To address these questions and gain insight into the motility capability of KIF3AC as a cargo transporter, we repeated the presteady-state kinetics experiments for microtubule association, ADP release, and ATP binding and pursued computational modeling coupled with parameter estimation. The results reveal that the catalytic properties of KIF3A and KIF3C were altered upon microtubule association to be catalytically similar, yet once in the processive run KIF3A remained fast with KIF3C continuing to be slow.…”
mentioning
confidence: 47%
“…Additional evidence that heterodimerization may alter the intrinsic catalytic properties of each motor domain as defined by the engineered homodimers KIF3AA, KIF3BB, and KIF3CC was supported by experimental results that showed that no mixtures of KIF3AA plus KIF3CC or KIF3AA plus KIF3BB could recapitulate the microtubule association and ADP release kinetics of KIF3AC or KIF3AB (49,50). puzzling results motivated this study to ask the following questions: 1) How do the properties of KIF3C affect the ATPase properties of KIF3AC?…”
mentioning
confidence: 71%
See 3 more Smart Citations